The franchise era : managing media in the digital economy - Fleury, James; Hartzheim, Bryan Hikari; Mamber, Stephen (Traditions in American cinema., 2019)
As Hollywood shifts towards the digital era, the role of the media franchise has become more prominent. This edited collection, from a range of international scholars, argues that the franchise is now an integral element of American media culture. As such, the collection explores the production, distribution and marketing of franchises as a historical form of media-making - analysing the complex industrial practice of managing franchises across interconnected online platforms. Examining how traditional media incumbents like studios and networks have responded to the rise of new entrants from the technology sector (such as Facebook, Apple, Amazon, Netflix and Google), the authors take a critical look at the way new and old industrial logics collide in an increasingly fragmented and consolidated mediascape.